2017
DOI: 10.1016/j.xphs.2017.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary Clearance Prediction: Species Scaling From Monkey, Dog, and Rat, and In Vitro–In Vivo Extrapolation of Sandwich-Cultured Human Hepatocytes Using 17 Drugs

Abstract: Hepatobiliary elimination can be a major clearance pathway dictating the pharmacokinetics of drugs. Here, we first compared the dose eliminated in bile in preclinical species (monkey, dog, and rat) with that in human and further evaluated single-species scaling (SSS) to predict human hepatobiliary clearance. Six compounds dosed in bile duct-cannulated (BDC) monkeys showed biliary excretion comparable to human; and the SSS of hepatobiliary clearance with plasma fraction unbound correction yielded reasonable pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 52 publications
4
52
0
Order By: Relevance
“…Studies with the hepatic uptake transporters (OATP1B1, OATP1B3, and OATP2B1) and renal organic anion transporters (OAT1, OAT2, and OAT3) were conducted based on a previously described method . For the hepatic uptake study in the SCHH system, a previously described methodology was used . Further details of experimental methodology and analytical methods are provided in .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with the hepatic uptake transporters (OATP1B1, OATP1B3, and OATP2B1) and renal organic anion transporters (OAT1, OAT2, and OAT3) were conducted based on a previously described method . For the hepatic uptake study in the SCHH system, a previously described methodology was used . Further details of experimental methodology and analytical methods are provided in .…”
Section: Methodsmentioning
confidence: 99%
“…14,37,38 For the hepatic uptake study in the SCHH system, a previously described methodology was used. 39,40 Further details of experimental methodology and analytical methods are provided in Supplemental Material S1.…”
Section: Transport Study In Transfected Hek293 Cells and Schh Modelmentioning
confidence: 99%
“…As reference compounds, four OATP1B substrate drugs (atorvastatin, pitavastatin, rosuvastatin, and valsartan) were administered simultaneously; the major clearance pathway of which is hepatic elimination by metabolism (atorvastatin) or biliary excretion (pitavastatin, rosuvastatin, and valsartan). [19][20][21][22] To our knowledge, this is the most comprehensive clinical assessment of the dose-dependent inhibition of OATP1B to date, and we were able to identify three new OATP1B biomarkers (glycodeoxycholate-3-sulfate (GDCA-S), glycodeoxycholate-3-glucuronide (GDCA-G), and glycochenodeoxycholate-3-glucuronide, (GCDCA-G)). Importantly, the performance of CP-I, a widely studied OATP1B biomarker, was confirmed, and at least four additional biomarkers (D-BIL, GCDCA-G, GCDCA-S, and hexadecanedioic acid (HDA)) were able to readily distinguish OATP1B inhibition by rifampicin at three different dose levels.…”
Section: Articlementioning
confidence: 99%
“…For renal secretion, measurements in organic anion transporter-transfected human embryonic kidney cells successfully predicted renal clearance of 31 diverse drugs [42] while a mechanistic model for passive tubular reabsorption was verified with a large dataset of drugs [43]. For hepatobiliary clearance, it was recently demonstrated that data from sandwich-cultured hepatocytes and a consistent IVIVE approach could predict in humans for 17 diverse drugs [44]. Furthermore, mechanistic IVIVE from the sandwich-cultured model, utilising transporter expression data in-vitro and in-vivo improved prediction for rosuvastatin in the rat [45].…”
Section: Metabolism and Eliminationmentioning
confidence: 95%
“…Furthermore, mechanistic IVIVE from the sandwich-cultured model, utilising transporter expression data in-vitro and in-vivo improved prediction for rosuvastatin in the rat [45]. It has also emerged that monkeys are a valuable model for the verification of hepatic disposition for transported molecules [44] particularly for substrates of the organic anion transporting polypeptide transporter [35]. Examples of complex PBPK models incorporating enzyme and transporter kinetics from in-vitro studies already exist and should become more common in the future as models evolve [46].…”
Section: Metabolism and Eliminationmentioning
confidence: 99%